The dynamics of business ecosystem identity: An ethnographic study on an Indian microenterprise clusters. Issue 3 (24th October 2019) - Panda, Debadutta Kumar
Abstract : Purpose: The purpose of this paper is to examine how business ecosystems evolve, what is the identity of business ecosystem and is the ecosystem identity static or dynamics. To understand the above questions, this paper is conducted on stone carving clusters in India. Design/methodology/approach: The author engaged the ethnographic approach in this study. To sample stone carving clusters of India, the author followed the snowball sampling method. Further, the author did collect the information by informal personal discussions, focus group discussions and participant observations. Furthermore, the thematic analysis and interpretative phenomenological analysis were applied to process the data. The validity and reliability of the method was ascertained by testing the credibility, dependability, confirmability and transferability. Findings: The author found that the business ecosystem of stone carving was dynamic, and it was transformed from the buyer-driven ecosystem to the supplier-driven ecosystem. The identities of the early stage business ecosystem and the late stage ecosystem were analyzed through product, network and information flow. The author developed a structural framework to conceptualize the identity domain of the business ecosystem and the author named it as "nature-conduct-performance model." Also, the author conceptualized the identity evolution, the influence of social system on business ecosystem identity, and identity-based conflicts and identity-based cooperation in the stone carving business ecosystem. Originality/value: This study is making additional theoretical contribution in conceptualize the business ecosystem from the identity construct.